Independent Tendency of ACE2 and GRP78 Expression in SARS-CoV2 Infection - Arya Adiningrat; Sekar Hasna Khairunnisa (Universitas Muhammadiyah Yogyakarta, 2022)
Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV2) is a virus that attacks the respiratory tract and causes the COVID-19 pandemic. This virus utilizes the host receptor as a cellular entry. Angiotensin-converting enzyme 2 (ACE2) has been assumed to be the essential host receptor for SARS-CoV2 infection. Furthermore, another costimulatory molecule, such as glucose-related protein 78 (GRP78), has also been reported. However, there are several inconsistent clinical data that could be observed regarding these molecules' involvement during SARS-CoV2 infection. This study aims to observe the possible involvement of ACE2 and GRP78 during the infection phase through gene expression profile analysis. Clinical specimens used in this study were taken in positive and negative clinical samples after the standard swab sampling procedure from both oropharyngeal and nasopharyngeal swabs. Subsequently, nucleic acid samples were proceeded by conventional Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR) to analyze the expression of ACE2 and GRP78. Agarose gel electrophoresis was then performed before the densitometric analysis. Statistical analysis using Mann-Whitney Test and Independent Sample t-Test was applied to justify the gene profile difference between ACE2 and GRP78. Our study suggested the enhancement tendency while they were not statistically significant in both ACE2 and GRP78 expression from the positive SARS-CoV2 samples.